Clinical and serological characteristics of symptomatic infection with seasonal human coronaviruses OC43, HKU1, NL63, and 229E in community-dwelling older adults - Verheul, Marije K.; Hendriks, Marion; de Melo, Caroline Vilas Boas; van Tol, Sophie; Godeke, Gert-Jan; van Binnendijk, Rob; Luytjes, Willem; Reusken, Chantal; van Beek, Josine (Frontiers in Virology, 2023)
Respiratory infections are a common cause of illness in older adults, potentially resulting in severe morbidity or mortality. While up to 10% of respiratory infections in this population are caused by one of the four human coronaviruses (hCoVs) -OC43, -HKU1, -NL63 and -229E, data on hCoV epidemiology and immunological responses is limited in community-dwelling older adults. In addition, it is often difficult to distinguish and identify distinct hCoV infections. Therefore, both clinical characteristics and the possibility to use serology to identify recent infections were investigated. Clinical characteristics and humoral immune responses were studied in community-dwelling older adults who presented with hCoV-related symptomatic influenza-like illness (ILI). Serum antibodies specific for each hCoV were identified by protein micro-array using recombinant spike proteins. Symptoms of participants with molecular confirmation of hCoV infection were difficult to distinguish from other viral pathogens causing ILI. Overall, severity based on a cumulative symptom score was less for hCoV compared to the other ILI-causing infections present in the study. Furthermore, symptom score did not correlate with changes in antibody levels. Using single serum samples to identify recent infections resulted in limited distinction between infections with ROC AUC values between 0.5 and 0.7 depending on the hCoV. However, paired serology samples collected at acute and recovery timepoints with an 8-week interval show a type-specific antibody boosting with ROC AUC values between 0.78 and 0.96 depending on the hCoV. Although clinical characteristics are comparable between hCoVs, analysis of antibody kinetics may provide an alternative method to identify recent hCoV infections.